King's cross : the story of the world in the life of Jesus - Keller, Timothy J., 1950- (New York, N.Y. : Dutton Redeemer, 2011)
Presents a revelatory examination of the life of Christ as told in the Gospel of Mark, inviting readers to review their personal relationships with God with a greater understanding of historical events.
Includes bibliographical references (p. 231-236).
Keywords: Jesus Christ -- Person and offices -- Biblical teaching; Bible. -- Criticism, interpretation, etc